Nordic war stories : World War II as history, fiction, media, and memory - Stecher-Hansen, Marianne (Worlds of memory, 2021)
Situated on Europe's northern periphery, Denmark, Finland, Iceland, Norway, and Sweden found themselves caught between warring powers during World War II. Ultimately, these nations survived the conflict as sovereign states whose wartime experiences have profoundly shaped their historiography, literature, cinema and memory cultures. Nordic War Stories explores the commonalities and divergences among the five Nordic countries, examining national historiographies alongside representations of the war years in canonical literary works, travel writing, and film media. Together, they comprise a valuable companion that challenges the myth of Scandinavian homogeneity while demonstrating the powerful influence that the war continues to exert on national identities.